2000
DOI: 10.1080/03050620008434963
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of multi‐country political conflict/cooperation interdependence

Abstract: Previous investigations of dynamic conflict actions and reactions among major countries have generally assumed the unit of analysis to be either a dyad or a triad. Our objective of the papais to explore this assumption. The empirical analysis employs quarterly political conflict/cooperation among the United States, the (former) Soviet Union, China, Japan, and (West) Germany from 19S0 to 1991. The model consists of a system of dynamic multiple regression equations. Various groups formed among mese countries are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The VAR model was initially proposed by Sims (1980) to explore the interactions among macro-economic variables and it was introduced to study the interactions between countries (e.g. Goldstein, 1991;Kang and Reuveny, 2000;Pang and Liu, 2019). We selected the VAR model for its flexible nature that does not require any presumptions (or restrictions) on the direction of the causality between variables (Lu, 2001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The VAR model was initially proposed by Sims (1980) to explore the interactions among macro-economic variables and it was introduced to study the interactions between countries (e.g. Goldstein, 1991;Kang and Reuveny, 2000;Pang and Liu, 2019). We selected the VAR model for its flexible nature that does not require any presumptions (or restrictions) on the direction of the causality between variables (Lu, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Goldstein and Freeman (1991) and Goldstein (1992) combined event data-COPDAB, WEIS, and ASHLEY-to quantitatively investigate USA-Soviet-China interactions from the 1950s to the 1980s, and showed the importance of reciprocity and the third country's influence in their interactions. Kang and Reuveny (2000) studied the political interactions among the USA, Soviet, China, Japan, and (West) Germany from 1980 to 1991 based on the COPDAB and WEIS data. They found that minor powers significantly influenced bilateral or trilateral relations between the superpowers.…”
Section: Introductionmentioning
confidence: 99%